Three 9-Year-Old Pupils from Sekolah Rendah Tahfiz Negeri Pahang Create Hologram Display Innovation, Win Gold at CITREX 2025 - Nur Hartini, Mohd Hatta (UMPSA, 2025)
PEKAN, 3 July 2025 – At only nine years old, three pupils from Sekolah Rendah Tahfiz Negeri Pahang (SRTNP), Muhammad Iqbal Qayyum Mat Yusri, Muhammad Irfan Mikhail Adnan, and Muhammad Taqiyuddin Mohd Tarmizi, successfully created a hologram display innovation and won a gold medal at the 2025 Creation, Innovation, Technology & Research Exposition (CITREX 2025).